Risk assessment of toxic residues among some freshwater and marine water fish species - Hussein, Mohamed A.; Morsy, Nanis S.; Mahmoud, Abdallah F.; Darwish, Wageh S.; Elabbasy, Mohamed T.; Zigo, František; Farkašová, Zuzana; Rehan, Ibrahim F. (Frontiers in Veterinary Science, 2023)
Egypt has several beaches, as well as the Nile River and a few lakes, therefore it could compensate for the lack of protein in red meat with fish. Fish, on the other hand, may become a source of heavy metal exposure in humans. The current study was to assess the level of five toxic metals lead (Pb), cadmium (Cd), mercury (Hg), arsenic (As), and aluminum (Al), in six species of Oreochromis niloticus (O. niloticus), Mugil cephalus (M. cephalus), Lates niloticus (L. niloticus), Plectropomus leopardus (P. leopardus), Epinephelus tauvina (E. tauvina), and Lethrinus nebulosus (L. nebulosus) collected from the El-Obour fish market in Egypt. The residual concentrations of the tested toxic metals in the examined O. niloticus, M. cephalus, L. niloticus, E. tauvina, P. leopardus, and L. nebulosus were found to be higher than the European Commission's maximum permissible limits (MPL) for Pb and Cd by 10% and 20%, 15% and 65%, 75% and 15%, 20% and 65%, 15% and 40%, and 25% and 5%. In contrast, 30% of L. niloticus exceeded the Hg (MPL). It was shown that the average of estimated daily intake (EDI), target hazard quotients (THQ) in fish samples are below safety levels for human consumption and Hazard index (HI˂1). From the human health point of view, this study showed that there was no possible health risk to people due to intake of any studied species under the current consumption rate in the country.